VD_FINDINFO AP / 2014 / 5 vom 18. Februar 2014 - VD Tribunal cantonal (2014)
TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS, RADIATION DU RÔLE | 109 al. 1 CPC (CH), 109 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 241 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)